Hyperchloremia Is Associated With Poorer Outcome in Critically Ill Stroke Patients - Huang, Kaibin; Hu, Yanhong; Wu, Yongming; Ji, Zhong; Wang, Shengnan; Lin, Zhenzhou; Pan, Suyue (Frontiers in Neurology, 2018)
Background and Purpose: This study aims to explore the cause and predictive value of hyperchloremia in critically ill stroke patients. Methods: We conducted a retrospective study of a prospectively collected database of adult patients with first-ever acute ischemic stroke (AIS) or intracerebral hemorrhage (ICH) admitted to the neurointensive care unit (NICU) of a university-affiliated hospital, between Jan 2013 and Dec 2016. Patients were excluded if admitted beyond 72 hours from onset, if they required neurocritical care for less than 72 hours, and were treated with hypertonic saline within 72 hours, or had creatinine clearance less than 15 mL/min. Results: Of 405 eligible patients, the prevalence of hyperchloremia ([Cl-] ≥ 110 mmol/L) was 8.6% at NICU admission ([Cl-]0) and 17.0% within 72 hours ([Cl-]max). 38 (9.4%) patients had new-onset hyperchloremia and 110 (27.1%) had moderate increase in chloride (△[Cl-] ≥ 5 mmol/L; △[Cl-] = [Cl-]max - [Cl-]0) in the first 72 hours after admission, which were found to be determined by the sequential organ failure assessment (SOFA) score in multivariate logistic regression analysis. Neither total fluid input nor cumulative fluid balance had significant association with such chloride disturbance. New-onset hyperchloremia and every 5 mmol/L increment in △[Cl-] were both associated with increased odds of 30-day mortality and 6-month poor outcome, although no independent significance was found in multivariate models. Conclusions: Hyperchloremia tends to occur in patients more severely affected by- AIS and ICH. Although no independent association was found, new-onset hyperchloremia and every 5 mmol/L increment in △[Cl-] were related to poorer outcome in critically ill AIS and ICH patients .